N-Acetylcysteine Therapy and Hospital Length of Stay Among SARS-CoV-2 Delta Variant Patients - Irma Susanti; Nurul Qiyaam; Muhtaromah; Ifa Aris Suminingtyas (Alma Ata University Press, 2026)
Background: The SARS-CoV-2 Delta variant surge was marked by high transmissibility and clinical severity, leading to substantial increases in hospitalizations and mortality. N-acetylcysteine (NAC) has been proposed as an adjunctive therapy for its mucolytic, antioxidant, and anti-inflammatory properties, particularly its ability to inhibit pro-inflammatory cytokines and restore glutathione levels. However, clinical evidence on its impact on hospital length of stay during the Delta variant surge remains limited. Objective: This study aimed to investigate the association between NAC therapy and length of hospital stay (LOS) among patients hospitalized with the SARS-CoV-2 Delta variant. Methods: A retrospective, cross-sectional observational study was conducted at Muhammadiyah Lamongan Hospital in Indonesia. Using purposive sampling, data were extracted from the medical records of 444 adult patients (≥18 years) with PCR-confirmed SARS-CoV-2 infection who were hospitalized between June and August 2021. All subjects received NAC therapy (≥1200 mg/day) as part of their clinical management. LOS was categorized as short (<10 days) or long (≥10 days) based on established clinical criteria. Results: The study population was predominantly male (50.5%), with the largest age group being 56–65 years (32.2%). The most prevalent comorbidities were pneumonia (60.4%), diabetes mellitus (21.0%), and hypertension (6.8%). Regarding clinical outcomes, 81.98% (n=364) of patients receiving NAC therapy were hospitalized for less than 10 days, while 18.02% (n=80) were hospitalized for 10 days or longer. Conclusion: Hospitalized patients with the SARS-CoV-2 Delta variant receiving NAC therapy predominantly had shorter hospital stays (≤10 days). These findings provide preliminary evidence of NAC's potential as a beneficial adjunctive treatment to expedite recovery.